The role of chief digital officer: Critical insights into an emerging field and road map for future research - Christofi, Michael (My University, 2024)
With the shift from the industrial era to the digital era and the increasing importance of digital transformation (DT) in organizations, a new role in the top management team of organizations emerged, that of the chief digital officer (CDO). This emerging phenomenon relates to a Chief (C) - level executive position, focused on the development and implementation of the digital strategy in organizations. To provide a better understanding of the nature of this phenomenon, as well as to develop the basis from which scholars to be based on for further developing this research stream, we conduct a systematic review of 29 articles published in highly esteemed business journals. By synthesizing the review findings, we identified emerging themes and core areas of inquiry, and clarified the nature, typologies and role of CDOs in organizations. Moreover, based on the synthesis and gaps identified in this review, as well as via the transfer of theory from the CEO-TMT literature, several research propositions are developed for scholars to test in the future and a new concept is emerged, that of the Multifunctional CDO Leadership. In conclusion this study provides various implications to both research and management practice.
Keywords: Chief Digital Officers; Digital transformation; Systematic review; Multifunctional CDO Leadership; Theory development